Decolorization kinetics of the direct red 23 diazo dye from zinc/cobalt mixed oxide semiconductor using oxalate as a precursor - Leo Neto, Vanildo Souza; Orcelli, Thiago; Silva, Marcelo Rodrigues da [UNESP]; Anaissi, Fauze Jac; Takashima, Keiko (Springer, 2016)
In this paper, we report the oxidation kinetics of the Direct Red 23 diazo dye through the UV irradiation of an aqueous suspension of zinc/cobalt mixed oxide semiconductor at 30 A degrees C. The zinc and cobalt mixed oxide was prepared by the thermal decomposition of their oxalates, containing 5, 10, and 20 % (w/v) cobalt and calcined at 400 A degrees C for 12 h. The characterization of these oxides was performed by X-ray diffraction, thermal and thermo-gravimetric analysis, X-ray dispersive energy spectrometry, scanning electron microscopy, diffuse reflectance spectroscopy, and textural analysis to understand the physical and chemical behavior of these materials. The suspension, formed by synthesized oxide and the Direct Red 23 diazo dye, was kept for 60 min in the dark and, subsequently irradiated during 210 min. The decolorization rate constant, k (obs) , was determined under pseudo-first order conditions, maintaining the semiconductor concentration much larger than the diazo dye concentration, using the maximum Direct Red 23 absorbance at 503 nm, and plotting the natural logarithm as a function of irradiation time at 30 A degrees C. All the synthesized mixed oxides displayed higher photocatalytic activity in comparison to commercial zinc oxide. From these, the oxide containing 5 % cobalt showed the highest photocatalytic activity, resulting in a rate constant for the Direct Red 23 diazo dye equivalent to 14.0 x 10(-3) min(-1) or 93 % decolorization at 30 A degrees C.
Keywords: Diazo dye oxidation; Heterogeneous photocatalysis; Photocatalytic activity; Oxide characterization